PROJECT-BASED LEARNING STRATEGY IN ISLAMIC RELIGIOUS EDUCATION TO ENHANCE STUDENTS' CRITICAL THINKING SKILLS - Sihabudin, Budi; Sukandar, Ahmad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Islamic Religious Education (PAI) has an important role in shaping the character, morals, and ethics of students. However, the challenge faced in PAI learning today is the lack of an approach that encourages students to think critically, analytically, and reflectively towards religious values ​​and the social realities around them. This study examines the effectiveness of implementing Project-Based Learning (PBL) integrated with Islamic values ​​in improving students' critical thinking skills in Islamic religious education. The research method used is a mixed-method approach with a quantitative experimental design, complemented by qualitative analysis through in-depth interviews, focus group discussions, and classroom observations. Data was collected through critical thinking ability tests, project documentation, and teacher and student perceptions regarding the relevance of Islamic values ​​in the learning process. The results showed that implementing the PBL model significantly increased the critical thinking ability score in the experimental group compared to the control group. In addition to improving cognitive performance, qualitative findings revealed increased motivation, engagement, and the formation of ethical and spiritual character among students. The study's conclusion confirms that the integration of Islamic values ​​in PBL enriches the cognitive dimension of learning and contributes to the development of students' character and theological insight as a whole. The implications of this research encourage the development of more adaptive and collaborative learning models, which Islamic religious educational institutions can adopt to answer the increasingly dynamic demands of 21st-century education.